EFFECTIVE TECHNIQUES OF TEACHING GENERAL ENGLISH (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
General English instruction remains a cornerstone of language education worldwide, ensuring learners develop functional competence across reading, writing, listening, and speaking. Yet, educators face myriad challenges in designing and implementing lessons that both engage students and promote sustained language growth. This scientific article examines effective techniques for teaching General English, drawing on influential theoretical models and empirical findings to highlight best practices. After reviewing major learning theories—ranging from behaviorist legacies to communicative and socio-constructivist approaches—the discussion zeroes in on practical strategies such as task-based learning, integrated skills development, and formative assessment. Results from various studies underscore the significance of communicative practice, technology integration, and learner-centered methodologies in bolstering motivation and proficiency. The conclusion recommends context-sensitive adaptations of these techniques and emphasizes ongoing professional development for teachers as key to ensuring students’ long-term language success.